2014
DOI: 10.1007/s10802-014-9923-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Autism-Related Symptoms into the Dimensional Internalizing and Externalizing Model of Psychopathology. The TRAILS Study

Abstract: Problems associated with Autism Spectrum Disorder (ASD) occur frequently in the general population and often co-occur with problems in other domains of psychopathology. In the research presented here these co-occurrence patterns were investigated by integrating a dimensional approach to ASDs into the more general dimensional framework of internalizing and externalizing psychopathology. Factor Analysis was used to develop hierarchical and bi-factor models covering multiple domains of psychopathology in three me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 47 publications
6
79
0
Order By: Relevance
“…Specifically, the best fitting models for these dimensions of temperament were ones in which there was both a common latent factor capturing what is shared across subscales in that construct as well as specific latent factors capturing what is unique to items in particular subscales. Importantly, while this bifactor modeling approach has not previously been applied to the EATQ or other measures of temperament, it has been found to best account for the structure of adult personality traits (e.g., Chen et al, 2012; Costa & McCrae, 1995), adolescent personality disorder traits (e.g., Roose, Bijttebier, Decoene, Claes, & Frick, 2010), and dimensions of psychopathology in both adults and adolescents (e.g., Caspi et al, 2014; Lahey et al, 2012; Noordhof, Krueger, Ormel, Oldehinkel, & Hartman, 2014; Tackett et al, 2013). Moreover, as we discuss below, these bifactor models enable investigation of links between other measures and both common and specific facets of each temperament dimension, revealing a more nuanced picture of how temperament affects adolescent functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the best fitting models for these dimensions of temperament were ones in which there was both a common latent factor capturing what is shared across subscales in that construct as well as specific latent factors capturing what is unique to items in particular subscales. Importantly, while this bifactor modeling approach has not previously been applied to the EATQ or other measures of temperament, it has been found to best account for the structure of adult personality traits (e.g., Chen et al, 2012; Costa & McCrae, 1995), adolescent personality disorder traits (e.g., Roose, Bijttebier, Decoene, Claes, & Frick, 2010), and dimensions of psychopathology in both adults and adolescents (e.g., Caspi et al, 2014; Lahey et al, 2012; Noordhof, Krueger, Ormel, Oldehinkel, & Hartman, 2014; Tackett et al, 2013). Moreover, as we discuss below, these bifactor models enable investigation of links between other measures and both common and specific facets of each temperament dimension, revealing a more nuanced picture of how temperament affects adolescent functioning.…”
Section: Discussionmentioning
confidence: 99%
“…We opted for the CSBQ instead of the SCQ to assess ASD symptoms, because we were specifically interested in current behavior, whereas the SCQ mainly refers to behavior at age 4–5 years. Multiple studies have shown that the CSBQ has good psychometric properties with regard to test–retest and interrater reliability, internal consistence of the scales (all reliability indices >0.75), and good criterion validity both for high-functioning children and for children with mild to moderate mental retardation (Hartman et al 2006; de Bildt et al 2009; Noordhof et al 2015; Jaspers et al 2013; Greaves-Lord et al 2013). For ASD symptoms only parent scores were provided, so it was not possible to combine them with teacher scores.…”
Section: Methodsmentioning
confidence: 99%
“…Most importantly, despite the variety of indicators available, we could not include all measures of psychopathology in our factor analysis. Among notable exclusions, psychotic and autism spectrum disorders seem to reflect unique factors [22, 94] but were precluded because of our data collection method. Other omitted disorders have been shown to primarily load onto Internalizing, such as social and specific phobias, panic and post-traumatic stress disorder [95] as well as onto Externalizing, like drug dependence and conduct disorder [23].…”
Section: Discussionmentioning
confidence: 99%